THE EFFECT OF IMPLEMENTING GREEN ACCOUNTING AND GOOD CORPORATE GOVERNANCE ON COMPANY VALUE: (Study of Industrial and Chemical Sector Companies Listed on the Indonesian Stock Exchange) - Ni Putu Ayu Rasita Nata Dewi; Henny Triyana Hasibuan (Transpublika Publisher, 2024)
The corporate value that has been owned by the company can influence public opinion. Good and high corporate value is able to increase public trust in the performance carried out by the company. The purpose of this study is to examine the effect of the implementation of green accounting and good corporate governance on corporate value. This study was conducted on industrial and chemical sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. Data were collected by observing the company's annual report and sustainability report. The sample in this study was taken using the purposive sampling method and obtained 58 companies as samples with a total of all samples used in five (5) periods being 248 samples. The analysis technique used in this study is multiple linear regression analysis. The results of the analysis show that green accounting has a significant negative effect on corporate value. Good corporate governance has a positive effect on corporate value.